Dislocations in an arbitrary angle wedge. Part II: Cracks in the wedge - Riddoch, DJ; Cwiekala, N; Hills, DA (SAGE Publications, 2021)
We describe a method for calculating the crack tip stress intensity factors for the problem of one or two cracks at the apex of an arbitrary angle wedge. The kernels for a dislocation in an arbitrary angle wedge described in part 1 of this paper are used extensively. Consideration is given to variations of crack length, crack angle and wedge angle.